Effects of Low Temperature on Somatic Embryos Growth, Maturation and Planlet Regeneration of Citrus Mandarin var Batu 55 (Citrus reticulata Blanco.) - Rosyidah, Mufidatur; Widoretno, Wahyu; Indriyani, Serafinah (The Journal of Experimental Life Science, 2015)
This study was aimed to determine the effect of incubation at 4°C temperature during multiplication stage of somatic embryos on growth, maturation and plantlets regeneration of citrus Mandarin var Batu 55. Globular somatic embryos were cultured on MT (Murashige & Tucker) medium and incubated at 4°C temperature for 0, 2, 4, 6, 8 weeks. Maturation of somatic embryos was induced by transfering globular somatic embryos on maturation medium (MT + 50 mgl-1 malt extract + 73 mM sorbitol + 73 mM galactose). Cotyledonary embryo was regenerated on MT medium + 50 mgl-1 malt extract + 30 gL-1 sucrose + 2 ppm GA3. The research showed that maturation of somatic embyos at 4°C temperature inhibited growth and maturation of somatic embyos. Fresh weight of somatic embryo incubated at 4°C for 2 weeks lower than fresh weight of embryo cultured without incubation at 4°C, and continuous decline in longer incubation period. Maturation percentage of embryos without incubation at 4°C temperature was 15%, but embryos incubated at 4°C temperature were lower than 9%. There was no effect of incubation at 4°C temperature during somatic embryos multiplication stage on plantlet regeneration percentage. Keywords: Citrus reticulata, maturation, plantlet regeneration, somatic embryo